2003
DOI: 10.1210/me.2002-0317
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Single-Chain Translation on the Structures of Two Chorionic Gonadotropin Yoked Analogs in α-β and β-α Configurations

Abstract: Human chorionic gonadotropin (hCG) is a placental-derived heterodimeric glycoprotein hormone, which, through the binding and activation of the LH receptor, rescues the corpus luteum and maintains pregnancy. The three-dimensional structure of hCG is known; however, the relevance of its fold to bioactivity is unclear. Although both subunits (alpha and beta) are required for activity, recent data with single-chain analogs have suggested a diminished role for the cystine knot and an intact heterodimeric interface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…11,13,16,[72][73][74][75][76] reflect the biological activities of the pituitary hormones could be answered only by comparing highly purified gonadotropins with homologous recombinant proteins, a setting not feasible in zebrafish due to its small size. Nevertheless, different recombinant gonadotropins, including single-chain and/or N-terminal His-tagged molecules (like the hormones used in this study), have been shown to elicit biological effects comparable to heterodimeric purified native hormones, which has been explained by the receptors' capacity to specifically recognize their ligands even if those are presented in different conformations (77)(78)(79)(80)(81)(82). Moreover, based on structural analysis of human FSH in complex with its receptor (80), the His tag used for purification is pointing away from the major receptor interaction sites, and therefore, it is unlikely to interfere with receptor activation.…”
Section: Discussionmentioning
confidence: 97%
“…11,13,16,[72][73][74][75][76] reflect the biological activities of the pituitary hormones could be answered only by comparing highly purified gonadotropins with homologous recombinant proteins, a setting not feasible in zebrafish due to its small size. Nevertheless, different recombinant gonadotropins, including single-chain and/or N-terminal His-tagged molecules (like the hormones used in this study), have been shown to elicit biological effects comparable to heterodimeric purified native hormones, which has been explained by the receptors' capacity to specifically recognize their ligands even if those are presented in different conformations (77)(78)(79)(80)(81)(82). Moreover, based on structural analysis of human FSH in complex with its receptor (80), the His tag used for purification is pointing away from the major receptor interaction sites, and therefore, it is unlikely to interfere with receptor activation.…”
Section: Discussionmentioning
confidence: 97%
“…These and additional studies indicated that not all the interactions between the a and b subunits as seen in the crystal structure of the heterodimer are mandatory for receptor binding and activation (Bhowmick et al, 1996;Fan and Hendrickson, 2005;Fox et al, 2001;Lapthorn et al, 1994). This is consistence with the notion that permissiveness exists in ligandreceptor interactions, at least as related to receptor binding and the generation of cAMP (Ben-Menahem et al, 1997;Fralish et al, 2003;Hiro'oka et al, 2000;Jackson et al, 1999;Moyle et al, 1987;Sato et al, 1997). However, the outcome of receptor activation with ligands that differ in their structure on steroidogenesis is less clear, and is highly relevant to fertility because of the heterogenous nature of the gonadotropins and the importance of the steroidogenic milieu for reproduction.…”
Section: Introductionmentioning
confidence: 96%
“…The generation of variants in the presence or absence of a linker sequence to space the tethered subunit domains, as well as switching their relative position, enabled to generate SC gonadotropin analogs with differences in the conformation (Argos, 1990;Ben-Menahem et al, 2001Garcia-Campayo and Boime, 2001;Grinberg et al, 2008;Sugahara et al, 1995Sugahara et al, , 1996b. Interestingly, gonadotropin analogs, mostly SC variants but also mutated heterodimers and nonpeptide mimetics, with a conformation that is different from that of the wild-type heterodimer, bound to the cognate receptor and stimulated cAMP formation, which is a key signaling mediator for steroidogenesis (Ben-Menahem et al, 1997;Fralish et al, 2003;Garcia-Campayo and Boime, 2001;Grossmann et al, 1997;Heikoop et al, 1997;Jackson et al, 1999;Maclean et al, 2004;Moyle et al, 1987;Perlman et al, 2003;Sato et al, 1997;Sugahara et al, 1995;van Straten et al, 2002;Weenen et al, 2004;Xing et al, 2001). These and additional studies indicated that not all the interactions between the a and b subunits as seen in the crystal structure of the heterodimer are mandatory for receptor binding and activation (Bhowmick et al, 1996;Fan and Hendrickson, 2005;Fox et al, 2001;Lapthorn et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, our qualitative analysis of glycosylation using specific lectins showed that the b-a single-chain as well as all secreted heterodimeric variants of eLH/CG exhibited not only mannosylated N-glycans but also galactosylated core 1 O-glycans as previously shown for recombinant equine glycoproteins expressed in Sf9 insect cells (Legardinier et al 2005b). Nevertheless, we can suppose that the three-dimensional conformation of single-chain eLH/CG could be altered when compared with heterodimeric eLH/CGs, as previously shown for hCG (Fralish et al 2003). Unlike previous studies which reported that eLH/CG b-a single chain was fully bioactive in vitro , Min et al 2004 and in vivo ( Jablonka-Shariff et al 2007), we report here that the b-a eLH/CG single-chain secretion by virus-infected insect cells was reduced when compared with heterodimeric eLH/CG and exhibited a slightly reduced in vitro LH bioactivity.…”
Section: Discussionmentioning
confidence: 53%